2009
DOI: 10.2139/ssrn.1508396
|View full text |Cite
|
Sign up to set email alerts
|

Shattered Dreams: The Effects of Changing the Pension System Late in the Game

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Among the studies reviewed in Table 12 that investigate gender heterogeneity, a majority find no significant differences in health outcomes between men and women. Moreover, studies that use a reform-based approach suggest that the potential gender differences are likely to be small or even zero (see, e.g., Hernaes et al 2013;Atalay and Barrett 2014;de Grip et al 2012). A similar picture is acquired from the related literature on the health effects of job loss.…”
Section: Resultsmentioning
confidence: 83%
“…Among the studies reviewed in Table 12 that investigate gender heterogeneity, a majority find no significant differences in health outcomes between men and women. Moreover, studies that use a reform-based approach suggest that the potential gender differences are likely to be small or even zero (see, e.g., Hernaes et al 2013;Atalay and Barrett 2014;de Grip et al 2012). A similar picture is acquired from the related literature on the health effects of job loss.…”
Section: Resultsmentioning
confidence: 83%
“…It is difficult, however, to measure individual productivity in the public sector. Using the same data as we use, De Grip et al (2012) recently showed that the unexpected drop in pension rights increases the likelihood of becoming depressed. Since depression affects productivity by causing mistakes at work, faulty products as well as increased sickness absence (see OECD, 2008), a mental health variable may serve as a useful alternative indicator for productivity.…”
Section: Alternative Productivity Indicatormentioning
confidence: 99%
“…4 These data were also used by De Grip et al (2012) who found a strong negative effect on the mental health of treated workers, and by Montizaan and Vendrik (2012), who study the impact of a reduction in pension wealth on life satisfaction and job satisfaction. Neither study considered heterogeneous effects that depend on negatively reciprocal motivations.…”
mentioning
confidence: 99%
“…In particular, overly optimistic beliefs may lead to under-saving. A recent study (De Grip et al 2012) even suggests that there is also a direct effect of expectations on well-being (implying that the effect of overly optimistic beliefs on life-time well-being is not unambiguously negative.) http://www.izajoels.com/content/1/1/2 It is therefore important to see whether different socio-economic groups have realistic views of the future or not.…”
Section: Introductionmentioning
confidence: 99%